Evaluation of a potato-based food product for acceptability, growth and diarrheal management in children - Guyo, Velonah (Vaal University of Technology, 2012)
Introduction: The World Health Organization (WHO) ranks diarrhoea as the second greatest killer of children below the age of five years. In South Africa, children’s illness and death is highly attributable to diarrhoea and malnutrition, with undernutrition and HIV infections predisposing children to the illness due to suppressed immune system. Therefore, the malnutrition status of children synergically worsens as a result of each episode of diarrhoea. This study was a contract research with Feed My Starving Children (NGO) for testing a potato-based food product for nutritional impact and relief for diarrhoeal episodes. Objectives: The purpose was to evaluate the acceptability of the product as a nutritional supplement for child growth and as a first food to complement oral rehydration and other efforts to reduce the impact and support the resolution of the symptoms of chronic and acute diarrhoea in children between the ages of two and thirteen in a Qwa-Qwa community (the experimental group), and in pre-schools in the Vaal region of Gauteng (the control group). Study design: A baseline cross-sectional and subsequent experimental study design was used. Methods: The study purposively enrolled children between the ages of 2-12 years, in experimental group of 96 and control group of 100. The study was conducted in three phases the first of which was a cross-sectional baseline survey in which the measurements included questionnaires to establish the nutritional status, diarrhoea prevalence in the two groups and sensory analysis questionnaire to establish acceptability of the potato-based based food product by the experimental group only. The anthropometric measurements included weight and height; the diarrhoea measurements included prevalence, duration and severity; while the sensory analysis included the taste, texture and appearance of the product. The second phase was the intervention programme in which the experimental group consumed the product for six weeks. The measurements taken included height, weight and diarrhoea episodes on weekly bases in the two groups. In the last phase all the measurements done at baseline were repeated to determine if the potato-based food intervention had an impact on the experimental group with respect to nutritional status and diarrhoeal mitigation as well as acceptability of the food product. Data analyses: All data was captured on Excel spreadsheets. The WHO growth standards were used to make a statistical comparison of the anthropometric indicators using WHO anthroPlus programme version 1.0.02. Data for diarrhoea and sensory analysis was analysed using the Statistical Package for Social Sciences (SPSS) version 20.0 for descriptive statistics (frequencies, means and standard deviations). Two tailed tests were done in order to determine any statistical differences between baseline and follow up measurements of both experimental and control groups. Results: Anthropometric: The total underweight in the experimental group decreased significantly (3.6 percent, p=0.015) while the control group increased by 2.0 percent (p=0.004). The results for stunting did not show any improvement specifically for the severely stunted children where stunting increased by 0.3 percent and 1.1 percent for the experimental and control group respectively. Conversely, the severely stunted and the stunted group decreased by 2.9 percent and two percent for the control group. As for severely wasted the results were unexpected where the experimental group had an increase of 0.1 percent while in the control group the severely wasted decreased to zero percent. However in both the experimental and control groups the number of wasted increased by 1.5 and 0.2 percent respectively. Diarrhoea: For the experimental group, there was a total reduction of diarrhoea incidence between baseline and immediately after the intervention (n=93, p=0000). Whereas for the control group the incidence remained largely unchanged with no statistical significant change of (n=93, p=063). The results showed that the intervention was effective in reducing stool frequency and consistency. Sensory analyses: The overall liking of the product was high. The two tailed significant tests results showed a high significant change in liking of the potatobased food product between baseline and follow up, texture (n=72, p=000) with a mean and standard deviation of 0.667 and 1.178, taste (n=72, p=0.0180) with a mean and standard deviation of 0.413 and 1.352 and appearance (p=0.00, n=72) mean and standard deviation of 0 .968±1.270 respectively. Conclusions and recommendations: The study revealed that the potato-based food intervention was effective in reducing the underweight, diarrhoea eradication and was very acceptable by the children due to its similarity to local dishes. Hence the potato-based food product can be used in similar intervention programmes as a first relief measure in management of diarrhoea. In future similar interventions should be carried out over a longer period of time inorder to get conclusive results especially where nutritional impact of the food intervention has to be measured.
M. Tech. (Department of Hospitality, Tourism and PR Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Malnutrition; Undernutrition; Diarrhoea; Sensory analysis; Potato-based food product; Dissertations, Academic -- South Africa.; Malnutrition in children -- South Africa.; Dietary supplements.; Children -- Nutrition -- South Africa.